Beneficial Effect of Intravenous Magnesium Sulphate in Term Neonates with Perinatal Asphyxia - Mahmood, Alina; Bazinjo, Attaullah; Riaz, Areeba; Rehman, Sana; Zahra, Seenam (Indus Journal of Bioscience Research, 2025)
Objective: To compare the efficacy of intravenous (IV) magnesium sulphate in treating neonatal hypoxia and enhancing immediate neurological outcomes. Study design: Randomized controlled trials. Settings: Neonatal intensive care unit (NICU) of Balochistan institute of child and health services Quetta. Study duration: January to April 2025. Materials & Methods: A total of 104 patients (52 in each group), both male and female infants and gestational ages gestational age ≥ 37 weeks presented with perinatal asphyxia were included. Babies who delivered by mothers who have had pethidine, phenobarbitone, magnesium sulphate (for pregnancy-induced hypertension), or any other medications that may depress the unborn child, Premature babies and Babies with congenital malformations or syndromic features were not included. Using a computer-generated random number table, the patients were split into two equal groups at random. Newborns in group A received additional magnesium sulphate doses of 250 mg/kg immediately after birth, followed by 125 mg/kg at 24 and 48 hours. This was administered as a 30-minute intravenous infusion of 5% dextrose. Neonates in group B was given all NICU protocol for birth asphyxia like electrolyte monitoring, seizure control and therapeutic hypothermia except magnesium sulphate therapy. Neurological evaluation was done using the Sarnat Classification or Sarnat Grading Scale at the time of admission and after 72 hours, and then when they were discharged back home. Efficacy was assessed at 72 hours of age in terms of poor neurological status, presence of seizures, mean time to establish feed, need of respiratory support and mortality. Results: In our study, neurological improvement, were recorded in 69.23%, absence of seizures in 75%, need of respiratory support in 34.62% and mortality in 11.54% babies in group A and 40.35%, 46.15%, 57.69% and 25.0% respectively in group B (p-value <0.05). Additionally, mean time for establishment of full oral feedings through sucking was documented as 17.83 ± 6.73 and 31.35 ± 9.45 hours, respectively (p-value = 0.0001). Conclusion: According to this research, magnesium sulfate may be essential for improving neurological recovery and early feeding readiness, which may lower the chance of long-term developmental problems.